Accelerated (45 mW/cm2) Transepithelial Corneal Cross-Linking for Progressive Keratoconus Patients: Long-Term Topographical and Clinical Outcomes - Zhang, Xiaoyu; Sun, Ling; Tian, Mi; Shen, Yang; Li, Meiyan; Zhao, Jing; Zhou, Xingtao (Frontiers in Medicine, 2020)
Aims: We characterized long-term clinical outcomes of accelerated (45 mW/cm2) transepithelial corneal cross-linking (ATE-CXL) for the treatment of progressive keratoconus. Methods: Forty-two eyes from 37 patients treated for keratoconus were observed. ATE-CXL was performed using riboflavin and pulsed-light ultraviolet treatment (45 mW/cm2, 7.2 J/cm2). Structural and functional measurements were made after 1 week and 1, 3, 6, 12, 24, 36, and 48 months subsequently. Corneal topographic parameters were observed using Scheimpflug topography (Pentacam software). Results: Surgery was uneventful in all subjects. Mean uncorrected (UDVA) and corrected distance visual acuity (CDVA) (logMAR) were 0.99 ± 0.58 and 0.44 ± 0.27 (P = 0.022), 0.24 ± 0.29 and 0.27 ± 0.35 (P = 0.601), at baseline and last follow-up, respectively. The pre-operative mean maximum keratometry (Kmax) value was 57.29 ± 9.13 diopters (D), and the thinnest corneal thickness (TCT) was 456.21 ± 44.66 μm. Mean Kmax was 56.67 ± 9.36 D, 4 years post-operatively (P = 0.781). TCT changed to 453.17 ± 46.76 μm at 4 years post-operatively (P = 0.780). Multiple linear regression indicated that patients with thinner pre-operative TCT (≤ 450 μm) showed decreasing post-operative average keratometry (Kavg) and increasing post-operative TCT. Patients with posterior central elevation (PCE) >80 μm showed decreasing post-operative Kavg as well as post-operative PCE. No complications were observed during follow-up. Conclusion: Stabilization after ATE-CXL was achieved for the treatment of keratoconus. The clinical efficacy of ATE-CXL in advanced keratoconus patients with thin corneal thickness and greater PCE will require further investigation.